Nekotorye osobennosti izucenija videoanaliza v sporte - Miftakhov, R. F.; Galyautdinov, M. I.; Sitdikov, A. M.; Fatkullov, I. R. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
Video analysis is a part of the modern sport. Analysts or video analysis departments appear in the structure of sports clubs, providing technical and technological aspects of video analysis in sports. In the research there are aspects, obtained as a result of the experience of teaching the subject of computer video analysis in sports for students of the Volga GAFKSIT. The goal of the research is to structure and develop the methodology of video analysis in sports. We considered the subject goals and objectives of video analysis in sports, determined the methods and technologies of video analysis in sports. Thus, the subject of video analysis in sports is a quantitative and qualitative indicator of the competitive and training activities obtained on the basis of video materials, as well as methods and ways for creating and processing video materials in sports. In particular, in accordance with the objectives of video analysis, it is possible to determine its types (ways): the collecting of statistical data by using video analysis, tactical video analysis, video analysis of biomechanical models and locomotion, video analysis in the organization of the training process, video analysis in scouting. The authors consider the example of realization the stages of video analysis in the structure of the sports club and according to the professional tasks. Since video analysis is a fairly new tool in sports, the considered features of its study contribute to the overall development of the methodology of video analysis in sports: the definition of the subject, tasks, methods and technologies. That allows improving the processes of the practical application of video analysis in the various sports and in the scientific research in the field of the physical culture and sports. Also, these methodological features can serve as a basis for determining the structure and contents of the training course on video analysis in sports.